Light Verb Constructions in German and Their Equivalents in Thai: A Contrastive Analysis through the Example of the Constitutional Texts - Natchapol Jutunka; Korakoch Attaviriyanupap (Future Science)
The present article is a contrastive analysis that deals with light verb constructions in German and their equivalents in Thai. The purpose of the study is to answer the following questions: 1) Which light verb constructions occur in the constitutional texts? How can they be categorized?; 2) Which forms occur in Thai as equivalents of German light verb constructions? How can they be categorized?; 3) What is the difference between the use of the light verb constructions in the original German text and in the German translation text?; 4) What is the difference between the use of the Thai equivalents of German light verb constructions in the original Thai text and in the Thai translation text? For the analysis, a bidirectional parallel corpus consisting of constitutional German and Thai texts and their translation into the other language was used. The results of this contrastive study can explain both differences and similarities between the two languages and the original and translated texts, such as morphological forms, active and passive meaning, and degree of structural strength, including the most frequently occurring light verb constructions and light verbs in the constitutional texts. In addition, it was found that Thai equivalents have a greater variety and the proportion of passive meaning in German is a little larger than in their Thai equivalents